Features of the Structure and Properties of Radiation Vulcanizates Based on Blends of Polybutadiene and Ethylene‐Propylene Diene Rubber. (10th August 2018) - El‐Nemr, Khaled F.; Ali, Magdy A. M.; Hassan, Medhat M.; Hamed, Huda E.
Abstract : Polybutadiene rubber (BR) was blended with ethylene‐propylene diene (EPDM) rubber on rubber mill with different weight ratios (100/0‐70/30‐50/50‐30/70‐0‐100), then application of gamma rays at different irradiation doses from 25 up to 150 kGy to induce crosslinking. Mechanical, physio‐chemical, and characterization of prepared blends are to be followed up as functions of the blend composition and the radiation absorbed dose. Mechanical properties like tensile strength (TS), elongation at break ( E b ), and tensile modulus ( M 100 ) were increased with increasing content of EPDM in blend composition. On the other hand, TS and M 100 increased with radiation dose, whereas the value of E b decreased with radiation dose. Physico‐chemical properties like gel fraction and volume fraction of rubber in swollen gel ( V r ) increased with increasing the content of EPDM rubber in blend formulation while the swelling ratio and soluble fraction decreased with increasing content of EPDM. On the other hand, the V r increased with radiation dose, whereas the values of soluble fraction and selling ratio ( Q ) decreased with radiation dose. Fourier transforms‐infrared measurements confirmed the compatibility between BR and EPDM rubber moieties in the blend matrix. J. VINYL ADDIT. TECHNOL., 25:E64–E72, 2019. © 2018 Society of Plastics Engineers